Patient's experience of psoriatic arthritis: a conceptual model based on qualitative interviews. Issue 3 (28th October 2020) - Ogdie, Alexis; Michaud, Kaleb; Nowak, Miroslawa; Bruce, Rachel; Cantor, Sarah; Hintzen, Carlijn; Mease, Philip J
Abstract : Introduction: Psoriatic arthritis (PsA) is a heterogeneous chronic inflammatory musculoskeletal disorder that manifests as peripheral arthritis, dactylitis, enthesitis and spondylitis. PsA results in significant burden that impacts quality of life of patients. We examined the signs, symptoms and impacts reported by patients with PsA, to characterise the patient experience of PsA and develop a conceptual model representing this patient experience. Methods: Semi-structured interviews were conducted with patients with PsA recruited through the FORWARD databank. Spontaneous and probed signs, symptoms and impacts of PsA were assessed. Patients rated the disturbance of these concepts on their lives using a scale from 0 ('does not disturb') to 10 ('greatly disturbs'). Signs, symptoms and impacts reported by >80% of patients with a disturbance rating of ≥5 were defined as salient concepts. Recruitment continued until concept saturation was achieved. Results: 19 patients with PsA were interviewed. The interviews elicited 42 symptoms of which 8 had not been identified in a previous literature review encompassing 15 relevant articles. The most salient signs and symptoms elicited in the interviews were joint pain, skin symptoms, stiffness, swollen/inflamed joints and fatigue all with moderate to high disturbance ratings (range: 5.5–7.8). The most salient impacts were sleep disturbance, physical disability, effects on daily activities and feelings of frustration with also moderate to high disturbance ratings (range: 6.1–7.4). Conclusions: The interviews highlighted the adverse impact PsA has on the patient's life and may inform on outcome variables or areas suitable to be assessed in PsA studies.